2005
DOI: 10.1007/s00442-005-0253-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of soil N-cycling in model ecosystems of Fennoscandian boreal forests

Abstract: The low plant productivity of boreal forests in general has been attributed to low soil N supply and low temperatures. Exceptionally high productivity occurs in toe-slope positions, and has been ascribed to influx of N from surrounding areas and higher rates of soil N turnover in situ. Despite large apparent natural variations in forest productivity, rates of gross soil N mineralization and gross nitrification have never been compared in Fennoscandian boreal forests of contrasting productivity. We report contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
60
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 64 publications
10
60
3
Order By: Relevance
“…Also, as expected (e.g. Swift et al 1979;Scheu 1997;van der Krift and Berendse 2001;Högberg et al 2006;Parton et al 2007), less recalcitrant species showed higher rates of respiration and net N-mineralization, if significantly so only for beech compared to spruce. Beech had also higher net N-mineralization per unit C respired than spruce, even in the mineral topsoil, which may be due to its higher N-content (Bagherzadeh 2004;Zhang and Makeschin 2004).…”
Section: Differences In N-cycling Between Speciessupporting
confidence: 84%
See 4 more Smart Citations
“…Also, as expected (e.g. Swift et al 1979;Scheu 1997;van der Krift and Berendse 2001;Högberg et al 2006;Parton et al 2007), less recalcitrant species showed higher rates of respiration and net N-mineralization, if significantly so only for beech compared to spruce. Beech had also higher net N-mineralization per unit C respired than spruce, even in the mineral topsoil, which may be due to its higher N-content (Bagherzadeh 2004;Zhang and Makeschin 2004).…”
Section: Differences In N-cycling Between Speciessupporting
confidence: 84%
“…However, the lack of litter quality effects on N-cycling seems contradictive to other literature reports (e.g. Scheu 1997;van der Krift and Berendse 2001;Högberg et al 2006;Parton et al 2007). However, when looking more closely, effects of higher litter quality may partly be attributed to higher litter input, which may also increase (van der Krift and Berendse 2001; Högberg et al 2006).…”
Section: Differences In N-cycling Between Speciescontrasting
confidence: 76%
See 3 more Smart Citations